Evolución de los conceptos y paradigmas que orientan la gestión ambiental ¿cuáles son sus limitaciones desde lo glocal? (2014)
In this article was made an analysis of the chronological evolution of different paradigms and concepts related to the environmental management (EM). the review highlights those that have impacts on the guidance of the EM in the country and the concept of associated development, as well as the considered approaches and dimensions for establishing the relations between them. Although the environmental management is one of the public functions shared with the society, the implemented model of EM has been unidirectional and this limited the inter institutional interaction with the communities and the interdisciplinary relations. If this situation have a glocal-logic point of view in different ecosystems and regions, the predominance of the economic growth approach is evident with a low interaction between know-how and knowledge, that circumstance restrict the construction of sustainable management alternatives and generate environmental actions isolated. Key words: management, ecosystems, environment, paradigm. Key words: management, ecosystems, environment,paradigm.